ROS: Executioner of regulating cell death in spinal cord injury - Yin, Zhaoyang; Wan, Bowen; Gong, Ge; Yin, Jian (Frontiers in Immunology, 2024)
The damage to the central nervous system and dysfunction of the body caused by spinal cord injury (SCI) are extremely severe. The pathological process of SCI is accompanied by inflammation and injury to nerve cells. Current evidence suggests that oxidative stress, resulting from an increase in the production of reactive oxygen species (ROS) and an imbalance in its clearance, plays a significant role in the secondary damage during SCI. The transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) is a crucial regulatory molecule for cellular redox. This review summarizes recent advancements in the regulation of ROS-Nrf2 signaling and focuses on the interaction between ROS and the regulation of different modes of neuronal cell death after SCI, such as apoptosis, autophagy, pyroptosis, and ferroptosis. Furthermore, we highlight the pathways through which materials science, including exosomes, hydrogels, and nanomaterials, can alleviate SCI by modulating ROS production and clearance. This review provides valuable insights and directions for reducing neuronal cell death and alleviating SCI through the regulation of ROS and oxidative stress.